Climate-Induced Hybrid Zones in Mammalian Species (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
Climate change is reshaping species geographic ranges, bringing previously allopatric taxa into secondary contact and generating novel hybrid zones whose dynamics differ fundamentally from historically established zones. This study characterised seven climate-induced hybrid zones in European and Central Asian mammalian species pairs spanning three orders (Carnivora, Rodentia, Lagomorpha), all formed or substantially expanded within the last 50 years, usingwhole-genome SNP data (RADseq; 286 individuals; mean 12,484 SNPs) combined with historical museum specimen georeferencing and species distribution modelling to quantify zone formation timing, current width, and genomic admixture architecture. All seven zones were confirmed as recent (